(untitled) - Manahan, Stanley E. (Boca Raton, 2009)
Fundamentals of Environmental Chemistry, Third Edition expands the scope of book to include the strongly emerging areas broadly described as sustainability science and technology, including green chemistry and industrial ecology.
Keywords: Environmental chemistry,Hóa học môi trường